2011
DOI: 10.1111/j.1600-0536.2011.01942.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of patch tests in clindamycin-related drug eruptions

Abstract: SummaryBackground. Patch tests help to confirm the aetiology of the cutaneous adverse drug reactions involving delayed hypersensitivity mechanisms, but the results vary with the pattern of skin reaction and the culprit drug. Objectives. To analyse the results of patch tests in patients with cutaneous adverse drug reactions imputable to clindamycin and assess their contribution to the diagnosis. Patients and methods. Between 2005 and 2009, we studied patients with delayed cutaneous adverse drug reactions follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
3
26
0
2
Order By: Relevance
“…Whilst IDT may be associated with an increased risk of systemic events, 93, 94 patch testing (PT) in severe cutaneous adverse reactions (SCAR) is considered safe. 9598 Guidelines suggest IDT can be performed, only after a negative PT and at least 6 weeks post skin healing. 99 …”
Section: Cross-reactivity and Cross-checking: The Importance Of Side Chmentioning
confidence: 99%
“…Whilst IDT may be associated with an increased risk of systemic events, 93, 94 patch testing (PT) in severe cutaneous adverse reactions (SCAR) is considered safe. 9598 Guidelines suggest IDT can be performed, only after a negative PT and at least 6 weeks post skin healing. 99 …”
Section: Cross-reactivity and Cross-checking: The Importance Of Side Chmentioning
confidence: 99%
“…24,25 Em relação à carbamazepina demonstrámos que nos cinco casos de DRESS, a hipersensibilidade retardada ao anticonvulsivante se manteve positiva, após um tempo mediano de 12,0 anos. A reprodutibilidade destes testes tem sido apenas descrita de forma esporádica, em alguns relatos de caso, AMX -amoxicilina; AMP -ampicilina; TE -testes epicutâneos; *sem diferença estatisticamente significativa em relação ao género (p= 0,6, teste qui--quadrado), idade (p = 0,9, teste Kruskal-Wallis) ou intervalo entre testes (p = 0,1, teste Kruskal-Wallis)…”
Section: Discussionunclassified
“…In recent studies, IDT has been suggested to be more sensitive than patch testing (PT) for T-cell-mediated ADRs [64]. However, in the setting of serious T-cell-mediated ADRs, PT is still considered “safer” than delayed-SPT/IDT [65,66]. The details of PT and IDT for T-cell-mediated ADRs are described below and a summary of T-cell-mediated ADRs is provided in Table 2.…”
Section: Historical Approaches To T-cell-mediated Hypersensitivitiesmentioning
confidence: 99%
“…The sensitivity of PT varies, however, and is highest for DRESS (32–80%) [112,113] and AGEP (58–64%) [112,114], and lowest for SJS/TEN (9–24%) [112,114] and MPE (10–40%) [65,113]. Patch testing lacks an appropriate positive control and results may be difficult to interpret in patients who are on immunosuppressants that impact T-cell-mediated immunity.…”
Section: Historical Approaches To T-cell-mediated Hypersensitivitiesmentioning
confidence: 99%
See 1 more Smart Citation